1989
DOI: 10.1530/jrf.0.0860577
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of bovine follicular oocytes by frozen-thawed spermatozoa in the presence of caffeine and heparin

Abstract: Bovine follicular oocytes matured in culture were inseminated with frozen-thawed spermatozoa which were either preincubated for 5-5.5 h or not preincubated in a medium with caffeine (5 mM) and heparin (10 micrograms/ml). When the oocytes with cumulus and corona cells were inseminated, spermatozoa started to penetrate oocytes 3 h later regardless of whether spermatozoa were preincubated or not. However, a significantly higher proportion of oocytes was penetrated by preincubated than non-preincubated spermatozoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 11 publications
(16 reference statements)
3
24
0
Order By: Relevance
“…Sperm were capacitated in two ways: 1) treatment with 10 µM calcium ionophore A23187 for 3 min [13], or 2) treatment with 10 mM caffeine-sodium benzoate (Sigma) and 20 µg/ml heparin (170 USP units/ml; Sigma) for 60 min [14]. After washing the chemicals out, the corresponding sperm suspension 1 or 2 was prepared at the concentration of 5 or 25 10 6 sperm/ml, respectively.…”
Section: Capacitation Of Spermatozoamentioning
confidence: 99%
“…Sperm were capacitated in two ways: 1) treatment with 10 µM calcium ionophore A23187 for 3 min [13], or 2) treatment with 10 mM caffeine-sodium benzoate (Sigma) and 20 µg/ml heparin (170 USP units/ml; Sigma) for 60 min [14]. After washing the chemicals out, the corresponding sperm suspension 1 or 2 was prepared at the concentration of 5 or 25 10 6 sperm/ml, respectively.…”
Section: Capacitation Of Spermatozoamentioning
confidence: 99%
“…Under the anaerobic conditions in the medium covered with mineral oil, the respiration of preincubated spermatozoa introduced into fertilization medium with 5 mM caffeine might be over-stimulated by 5 mM caffeine, and consequently the motility of the spermatozoa may be decreased. In previous studies on bovine in vitro fertilization showing high fertilization rates in fertilization medium with caffeine [1][2][3][4][5][6][13][14][15][16][17][18], the sperm concentrations at the site of fertilization were very high and these high sperm concentrations might have made up for the disadvantage of 5 mM caffeine at fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi and Hanada have reported that caffeine in the medium appears to enhance the capacitating action of I-A [4]. Synergistic effects of caffeine and heparin on IVF have been reported in cattle [5,6]. Furthermore, caffeine in the fertilization medium accelerates sperm penetration in vitro in pigs [7][8][9] and mice [10].…”
mentioning
confidence: 99%
“…Unlike in vivo, the cumulus cells are tightly attached to the in vitro matured oocyte (Park et al, 1989). Several studies confirm that removal of cumulus cells strongly decreases developmental capacity (Cox et al, 1993;Zhang et al, 1995 …”
Section: In Vitromentioning
confidence: 99%